Dynamic analysis and oscillation elimination of brushless doubly fed wind power generation system during symmetrical voltage dips. Issue 2 (12th January 2021) - Nie, Pengcheng; Wang, Xuefan; Kong, Ming
Abstract: In the dynamics of grid‐connected operation of brushless doubly‐fed generators, grid voltage dips can cause the extreme imbalance between the voltage and the back electromotive forces in power winding. When these imbalances are combined with the influence of the inertia link composed of converter and generator, a serious over‐current and current oscillation forms in power winding and control winding. This paper gives a process analysis and proposes an improved control to the system during the low voltage ride through event. According to the mathematical model of the generators, the correlation between the power winding and control winding currents is established and then a fully equivalent simplified model is obtained accordingly. When the voltage suddenly drops to zero, the analytic expressions of power winding and control winding are calculated in the complex frequency domain and the influence factors of overshoot and oscillations are analyzed. The conventional control method relies on limited PI regulation that cannot eliminate the oscillations completely. It is found that after adjusting a proportional coefficient and eliminating the integral link of the control winding current controller, the order of the control system reduces. Therefore, the generation system can quickly recover to a steady state without oscillations. Finally, the analysis and improvement are verified by the simulation model and experimental results.